Optimizing Encapsulation: Comparative Analysis of Spray-Drying and Freeze-Drying for Sustainable Recovery of Bioactive Compounds from Citrus x paradisi L. Peels - Jolita Stabrauskiene; Lauryna Pudziuvelyte; Jurga Bernatoniene (MDPI AG, 2024)
Spray-drying and freeze-drying are indispensable techniques for microencapsulating biologically active compounds, crucial for enhancing their bioavailability and stability while protecting them from environmental degradation. This study evaluates the effectiveness of these methods in encapsulating Citrus x paradisi L. (grapefruit) peel extract, focusing on sustainable recovery from waste peels. Key objectives included identifying optimal wall materials and assessing each encapsulation technique's impact on microencapsulation. The investigation highlighted that the choice of wall material composition significantly affects the microencapsulation's efficiency and morphological characteristics. A wall material mixture of 17 g maltodextrin, 0.5 g carboxymethylcellulose, and 2.5 g β-cyclodextrin was optimal for spray drying. This combination resulted in a sample with a wettability time of 1170 (s), a high encapsulation efficiency of 91.41%, a solubility of 60.21%, and a low moisture content of 5.1 ± 0.255%. These properties indicate that spray-drying, particularly with this specific wall material composition, offers a durable structure and can be conducive to prolonged release. Conversely, varying the precise compositions used in the freeze-drying process yielded different results: quick wettability at 132.6 (s), a solubility profile of 61.58%, a moisture content of 5.07%, and a high encapsulation efficiency of 78.38%. The use of the lyophilization technique with this latter wall material formula resulted in a more porous structure, which may facilitate a more immediate release of encapsulated compounds and lower encapsulation efficiency.